'Different from What Has Hitherto Appeared on this Subject': John Clark, Writing Master and Accomptant, 1738. (21st November 2012) - Edwards, John Richard
<x xml:space="preserve">Abstract</x> This paper argues the importance, for the study of accounting history, of collecting evidence of accounting's past and of questioning its conventional wisdoms. It is known that Cronhelm (1818) explained in algebraic terms the mathematical relationship between assets, liabilities and capital reported in a balance sheet. It is also known that the balance sheet equation Assets (A) – Liabilities (L) = Capital (C) became a foundation for teaching bookkeeping as the twentieth century progressed. Current knowledge suggests that, during the first half of the twentieth century, this mathematical approach to teaching accounting gained a foothold in the United States based on the writings of Sprague and Hatfield, and also in Continental Europe. This paper reveals that, in the 1730s in England, John Clark cogently demonstrated an algebraically rooted understanding of the inter‐relationship between double entry bookkeeping and the structure of the balance sheet as exemplified by the above equation. The paper proves that journal‐oriented learning was not the exclusive training method employed by bookkeeping instructors during the early eighteenth century and raises the possibility that other teachers of bookkeeping were providing a more thoughtful education for aspiring clerks, bookkeepers, managers and businessmen than has hitherto been thought the case. This study also shows that accounting technologies do not continuously evolve towards their current state of elaboration, and that it is important for researchers to remain aware of plurality in patterns of accounting change and to be willing to embrace the full range of methodological approaches available for studying accounting phenomena.